Recent developments in ionization techniques for single-cell mass spectrometry - Zeng, Qingli; Xia, Meng-Chan; Yin, Xinchi; Cheng, Simin; Xue, Zhichao; Tan, Siyuan; Gong, Xiaoyun; Ye, Zihong (Frontiers in Chemistry, 2023)
The variation among individual cells plays a significant role in many biological functions. Single-cell analysis is advantageous for gaining insight into intricate biochemical mechanisms rarely accessible when studying tissues as a whole. However, measurement on a unicellular scale is still challenging due to unicellular complex composition, minute substance quantities, and considerable differences in compound concentrations. Mass spectrometry has recently gained extensive attention in unicellular analytical fields due to its exceptional sensitivity, throughput, and compound identification abilities.At present, single-cell mass spectrometry primarily concentrates on the enhancement of ionization methods. The principal ionization approaches encompass nanoelectrospray ionization (nano-ESI), laser desorption ionization (LDI), secondary ion mass spectrometry (SIMS), and inductively coupled plasma (ICP). This article summarizes the most recent advancements in ionization techniques and explores their potential directions within the field of single-cell mass spectrometry.based microextraction with ESI-MS for removal of matrix interference in single-cell analysis.